# 6d-9=1d+1

## Simple and best practice solution for 6d-9=1d+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6d-9=1d+1 equation:

Simplifying
6d + -9 = 1d + 1

Reorder the terms:
-9 + 6d = 1d + 1

Reorder the terms:
-9 + 6d = 1 + 1d

Solving
-9 + 6d = 1 + 1d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-1d' to each side of the equation.
-9 + 6d + -1d = 1 + 1d + -1d

Combine like terms: 6d + -1d = 5d
-9 + 5d = 1 + 1d + -1d

Combine like terms: 1d + -1d = 0
-9 + 5d = 1 + 0
-9 + 5d = 1

Add '9' to each side of the equation.
-9 + 9 + 5d = 1 + 9

Combine like terms: -9 + 9 = 0
0 + 5d = 1 + 9
5d = 1 + 9

Combine like terms: 1 + 9 = 10
5d = 10

Divide each side by '5'.
d = 2

Simplifying
d = 2`